1997
DOI: 10.1016/s0092-8674(00)80264-0
|View full text |Cite
|
Sign up to set email alerts
|

Self-Seeded Fibers Formed by Sup35, the Protein Determinant of [PSI+], a Heritable Prion-like Factor of S. cerevisiae

Abstract: The [PSI+] factor of S. cerevisiae represents a new form of inheritance: cytosolic transmission of an altered phenotype is apparently based upon inheritance of an altered protein structure rather than an altered nucleic acid. The molecular basis of its propagation is unknown. We report that purified Sup35 and subdomains that induce [PSI+] elements in vivo form highly ordered fibers in vitro. Fibers bind Congo red and are rich in beta sheet, characteristics of amyloids found in certain human diseases, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

26
521
2
5

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 587 publications
(554 citation statements)
references
References 39 publications
26
521
2
5
Order By: Relevance
“…The Ure2 system is therefore a useful model not only to investigate the prion concept, but also to understand the properties of Gln/ Asn-repeat proteins and hence the molecular basis of the related diseases. [27,29,58], Sup35 [114,115], Rnq1 [13], Het-s [22] and PrP [23,24,116,117]. The functional regions are as indicated.…”
Section: Introductionmentioning
confidence: 99%
“…The Ure2 system is therefore a useful model not only to investigate the prion concept, but also to understand the properties of Gln/ Asn-repeat proteins and hence the molecular basis of the related diseases. [27,29,58], Sup35 [114,115], Rnq1 [13], Het-s [22] and PrP [23,24,116,117]. The functional regions are as indicated.…”
Section: Introductionmentioning
confidence: 99%
“…This region may be further subdivided into the middle (M) domain, of unknown function, and the N-terminal (N) domain of 123 amino acids, required for [PSI + ] maintenance (Figure 1). The N domain plays a key role in the [PSI + ] phenomenon, being required for [PSI + ] propagation in vivo and solely responsible for Sup35p prion conversion and oligomerization into amyloid-like ®brils in vitro (Paushkin et al, 1997a, b;Glover et al, 1997;King et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…have at least three cellular components, [URE3], 3,4) [PSI þ ], [5][6][7] and [PIN þ ], [8][9][10] that persist in the cell in the same manner as mammalian prion; hence they are often referred to as yeast prions. The yeast prions are not only attractive research objects in themselves but also useful model experimental systems for elucidating conformational alteration of mammalian prion and polymerforming proteins in general.…”
mentioning
confidence: 99%
“…10,17) It has been found that Sup35, Sup35NM, and Sup35N form polymers in vivo and also in vitro. 7,[18][19][20] Since it is a common practice in these studies to construct a fusion gene in which glutathione S-transferase (GST: EC2.5.1.18) is combined with the peptide of interest and to introduce it into the E. coli expression system, we constructed a plasmid that carried a gene encoding GST-Sup35NM in which Sup35NM was fused to the C terminus of GST. Cells producing this fusion protein grew normally to the stationary phase, but their colony-forming ability in the stationary phase decreased much faster than that of the control cells.…”
mentioning
confidence: 99%